2017
DOI: 10.1016/j.snb.2016.09.067
|View full text |Cite
|
Sign up to set email alerts
|

A nanowell-based QCM aptasensor for rapid and sensitive detection of avian influenza virus

Abstract: In this study, a cost-effective nanowell structure was fabricated and utilized for the development of a nanowell-based quartz crystal microbalance (QCM) aptasensor for rapid, sensitive, and label-free detection of H5N1 avian influenza virus (AIV). A nanoporous gold film with a thickness of 120 nm and a pore size of ~20 nm was prepared using a metallic corrosion method. Then, the nanoporous gold film was immobilized onto a gold electrode surface using a self-assembled monolayer to form a nanowell-based electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 38 publications
1
44
0
Order By: Relevance
“…No clear linear portions of the concentrations of B. bifidum can be observed using mouse monoclonal antibody-AuNPs conjugation as detection layer. The results recorded in this study are very competitive with previous reports (Fung and Wong, 2001;Guo et al, 2012;Skládal, 2016;Della Ventura et al, 2017;Wang R. et al, 2017;Gao et al, 2018;Pohanka, 2018aPohanka, ,b, 2019. Table 1 showed the sensing performance comparison.…”
Section: Resultssupporting
confidence: 71%
“…No clear linear portions of the concentrations of B. bifidum can be observed using mouse monoclonal antibody-AuNPs conjugation as detection layer. The results recorded in this study are very competitive with previous reports (Fung and Wong, 2001;Guo et al, 2012;Skládal, 2016;Della Ventura et al, 2017;Wang R. et al, 2017;Gao et al, 2018;Pohanka, 2018aPohanka, ,b, 2019. Table 1 showed the sensing performance comparison.…”
Section: Resultssupporting
confidence: 71%
“…The nanostructuring approach increased the surface area of the electrode by 13 times, resulting in a 5-fold increase in the density of the immobilised aptamer. The nanowell aptasensor had a remarkable detection time of 10 min ( Wang et al, 2017 ), matching the assay time of commercial RDTs for influenza, which typically ranges between 10–30 min ( Cho et al, 2013 ).
Fig.
…”
Section: Qcm-based Biosensors For Prevalent Infectious Diseasesmentioning
confidence: 99%
“…Wang et al reported a label-free nanowell-based quartz crystal microbalance aptasensor for detecting H5N1 avian influenza virus (AIV). 115 A nanoporous gold film was prepared using metallic corrosion technique and immobilized onto a gold electrode surface. Then, a mixture of mercaptohexadecanoic acid (MHDA) and 1,6hexanedithiol (HDT) were applied on the gold electrode surface to form a nanowell-based electrode.…”
Section: Aptamer-based Sensorsmentioning
confidence: 99%